EVALUATION OF THE IMPACT OF EDUCATIONAL INTERVENTION FOR THE PROMOTION OF INNOVATIONS IN HEALTHY LIFESTYLES OF 17 PUBLIC SCHOOLS OF BARRANQUILLA, COLOMBIA - Mendoza-Charris, Humberto; Ricaurte-Rojas, Carlos; Maury Mena, Sara Concepcion; Alonso-Palacio, Luz Marina (Horizonte Sanitario, 2021)
Introduction: The impact of the training of primary teachers of a program for the adoption of innovations in health to prevent and / or control childhood obesity in 17 primary schools in Barranquilla (Colombia) was evaluated, using the Kirpatrick 4-Level Model. Materials and methods: The type of study is a retrospective cohort. The population was made up of 120 elementary school teachers from 13 public schools. A questionnaire was applied to evaluate the impact on satisfaction. For the impacts on learning, behaviour and results, the interview, and the development of demonstrations of knowledge and skills during the training sessions were used. Results: About 90% of the participants rated their satisfaction as "High" or "Very high". 89.10% asked that the educational program continue. Learning, measured in knowledge and skills; and attitude, measured in commitment, availability, and trust, had scores higher than 4.5 (scale from 1 to 5) in 73.5% of the participants in both categories. The impact of the results in the organization showed an increase in physical activity in 100.0% of the institutions while the incorporation of nutritional education in 61.5%. Discussion and conclusions: The application of the Kirpatrick model made it possible to determine the value generated by the training and estimate the return on expectations (ROE), while providing new elements that help to understand how innovations were being adopted. The study allowed us to ponder, not only to what extent the training impacted the level of learning, but also how this influenced the teacher's initial perception - according to which overweight and childhood obesity were basically the competence of the health sector - and then acquire a meaning for them closely linked to the academic training of primary school children, and easy to apply.